2018
DOI: 10.1002/smll.201800118
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Mass Production of Stabilized and Stealthy Liquid Metal Nanoparticles

Abstract: Functional nanoparticles comprised of liquid metals, such as eutectic gallium indium (EGaIn) and Galinstan, present exciting opportunities in the fields of flexible electronics, sensors, catalysts, and drug delivery systems. Methods used currently for producing liquid metal nanoparticles have significant disadvantages as they rely on both bulky and expensive high-power sonication probe systems, and also generally require the use of small molecules bearing thiol groups to stabilize the nanoparticles. Herein, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
143
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(144 citation statements)
references
References 42 publications
0
143
1
Order By: Relevance
“…Stable aqueous suspensions of LM nanodroplets are not only for electronic applications, but also exhibit great potential in medicine and therapy, such as drug delivery, photothermal therapy, and bioimaging . Water‐soluble surfactants, including cetrimonium bromide, poly(4‐vinyl‐1‐methyl‐pyridinium bromide), lysozyme, and trithiocarbonate‐functionalized brushed polyethylene glycol have been used to stabilize LM nanodroplets during and after sonication of bulk LMs in water . In addition, when LM nanodroplets in aqueous solution are placed at room temperature for 16 h or heated up to about 70 °C for 30 min, the spherical nanodroplets will be oxidized and dealloyed, resulting in the formation of rods of gallium oxide monohydroxide (GaOOH) and spherical indium nanoparticles .…”
mentioning
confidence: 99%
“…Stable aqueous suspensions of LM nanodroplets are not only for electronic applications, but also exhibit great potential in medicine and therapy, such as drug delivery, photothermal therapy, and bioimaging . Water‐soluble surfactants, including cetrimonium bromide, poly(4‐vinyl‐1‐methyl‐pyridinium bromide), lysozyme, and trithiocarbonate‐functionalized brushed polyethylene glycol have been used to stabilize LM nanodroplets during and after sonication of bulk LMs in water . In addition, when LM nanodroplets in aqueous solution are placed at room temperature for 16 h or heated up to about 70 °C for 30 min, the spherical nanodroplets will be oxidized and dealloyed, resulting in the formation of rods of gallium oxide monohydroxide (GaOOH) and spherical indium nanoparticles .…”
mentioning
confidence: 99%
“…2e) and 300 s (Fig. 2f) sonication time, as well as bPEG (Mn~20 kDa, see details in previous work 17 and Fig. S4 in ESI) grafted EGaIn NPs (Fig.…”
Section: Resultsmentioning
confidence: 72%
“…While most conventional metallic nanoparticles (NPs) are synthesized through a tedious bottomup approach (i.e., reducing precursor metal salts), the fluidic nature of liquid metals (LMs) enables facile methods to produce LM NPs. Disruptive forces induced by acoustic stimulation [10][11][12][13][14][15] , microfluidic devices 16,17 or shearing 18 have been utilized to break the LMs into nanosized particles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As analyzed by X‐ray diffraction, UV–vis spectroscopy, and transmission electron microscope (TEM), the resultant AgNPs were produced with high‐quality and monodispersity, owing to the rapid and efficient mixing in individual droplets. In another study, Tang et al also reported a droplet‐based microfluidic chip for efficiently producing eutectic gallium indium (EGaIn) NPs . The EGaIn precursor and suspension medium was respectively pumped into the T‐shaped microchannel which was widely used for generating microdroplets.…”
Section: Microfluidic Generation Of Npsmentioning
confidence: 99%